Residency is residency, work is work: a quali-quantitative study on the remote work of university professors during the COVID-19 pandemic (Research, Society and Development, 2021)
This is a quali-quantitative study that aims to understand the objective and subjective conditions experienced by Brazilian university professors in the face of emergency remote work, in the COVID-19 pandemic. Data from 508 respondents who answered the open question of a web survey were analyzed in five Categories of Reports on Remote Working Conditions (1. Home space; 2. The change from face-to-face to remote; 3. No complaints; 4. Reflections on illness; 5. Mixed). Sociodemographic, household and working conditions data were analyzed between reporting categories using the Pearson/Fischer chi-square test. Most professors were female (65%), 40 years or older (77%), married (65%), with children (64%) and lived with up to three people (74%). The reports classified in category 2 were prevalent (42.9%) and showed difficulties in social interaction; increased demand; feeling of exploration; and lack of institutional support. There was an association with sociodemographic data, number of rooms and residents, and some conditions for teleworking (p